Politik Luar Negeri Pemerintahan Susilo Bambang Yudhoyono Periode 2004 â 2009 terhadap Integrasi ASEAN - , Ambar Retnosih Widyantini, SIP. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The leadership of President Susilo Bambang Yudhoyono in the period 2004 - 2009 had to face a lot of problems both domestic and external problems. This government faced domestic problems like the conflict in Ambon, Papua and Aceh Movement. Transnationalism issues such as terrorism, global migration, trafficking and illegal logging, illegal fishing and diplomacy of border is still an interest topic of Indonesian foreign policy. Meanwhile the countries, members of the ASEAN still have chores about complexs security in the region, improve the country's economy, develop ASEAN identity, and face challenges of external state (East Asia, the EU, and the United States) The existence of these problems is the reason why this research is very important to do. This research is aimed to analyze the fundamental reasons Susilo Bambang Yudhoyono administration period 2004 - 2009 directs its foreign policy to encourage establishment of the ASEAN Community . What are the form foreign policy is realized and what are interests of President Susilo Bambang Yudhoyono with the establishment ASEAN Community in 2015. Issue linkage is the conceptual basis for analyzing this research. Foreign policy of a country in relation to international cooperation will be easier when analyzed by connecting a realm of issues with other domains in which each issue is different and each actor will get the goals. A state leader strategizing foreign policy within the framework securing the future of domestic interests and enhance position in ASEAN region and international politics. Concept of two-level games analyzed this strategy..